ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AGRESIVITAS PAJAK (Studi Empiris Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Meiriska Tri Wahyuningtyas, 15.05.52.0356; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2019)
This aims to analyze and test the effect ofleverage, liquidity, capital intensity, corporate social responsibility, independent commissioner, and firm size on tax aggressive on manufacturing companies listed on Indonesia Stock Exchange for the period 2015-2017. This study used a sample of 192 manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. The sample of this study was obtained by purposive sampling. The type of data used is secondary data. Research data were analyzed by analysis of multiple regression and the data’s tabulation was processed by software SPSS 23.0 for windows. The result showed that leverage, liquidity, and independent commissionerhas a significant negative effect on tax aggressive, while the capital intensity, corporate social responsibility (CSR), and firm sizehave insignificant positive effect on tax aggressive.